Os tambores da África reverberam aqui: o projeto batuque como prática decolonial na comunidade quilombola de São Pedro dos bois-AP - BARBOSA, Adrian Kethen Picanço (Universidade Federal do Pará, 2022)
This research has as its theme Quilombola School Education (EEQ). Within this modality of teaching, I will analyze the Batuque Project as a decolonial practice in the Quilombola community of São Pedro dos Bois, Amapá. The study follows the methodology of Orlando Fals Borda's Participatory Action Research (1978), updating it according to the perspective of decoloniality. My analysis of the Batuque Project in the aforementioned Quilombola community emphasizes the decolonial transformations promoted by Quilombola School Education. The research presents the decolonial practice within the State Quilombola School Teixeira de Freitas, which is the result of an education engaged and committed to the environment in which the institution is inserted.